Membangun Santripreneur Komunikatif melalui Pelatihan Pidato dan MC dalam Tiga Bahasa untuk Meningkatkan Kapasitas Kewirausahaan Sosial di Pondok Pesantren Salafiyah Al Choliliyah Pasuruan - Mukaromah, Ning; Rachmatika, Fajriyah; Suci Dian Sari, Agung; Suadi, Suadi; Nasihin, Khoirun (Humanist Journal, 2024)
This study aims to build communicative santripreneurs at Pondok Pesantren Salafiyah Al Choliliyah Pasuruan through speech and MC training in three languages as an effort to enhance the social entrepreneurship capacity of the santri. By emphasizing effective communication skills, this training aims to equip the santri with public speaking abilities and entrepreneurship-based skills that can open up opportunities for social business in the future. The results of this study are expected to strengthen the communication skills of the santri, boost their confidence, and encourage them to take an active role in the world of sustainable social entrepreneurship.